2020
DOI: 10.47577/technium.v2i3.575
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and Modeling the Factors Affecting Thermal Optimization and Dynamic Viscosity of Water Hybrid Nanofluid/Carbon Nanotubes via MOPSO using ANN

Abstract: Optimization is to find the best answer among existing situations. Optimization is used in the design and maintenance of many engineering systems to minimize costs or maximize profits. Due to the widespread use of optimization in engineering, this topic has grown a lot. In this paper, the optimization of multi-objective of Water Hybrid Nanofluid/Carbon Nanotubes is investigated. Multi-Objective Particle Swarm Optimization (MOPSO) algorithm has been used in order to maximize thermal conductivity and minimum vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They showed that the was the most influential factor among all model input parameters. Petrudi and Scurtu [ 19 ] modeled the k nf and viscosity by changing the temperature and the using ANNs. Their results show that the highest k nf and the lowest viscosity occur when a maximum temperature and are used.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the was the most influential factor among all model input parameters. Petrudi and Scurtu [ 19 ] modeled the k nf and viscosity by changing the temperature and the using ANNs. Their results show that the highest k nf and the lowest viscosity occur when a maximum temperature and are used.…”
Section: Introductionmentioning
confidence: 99%